2012
DOI: 10.1002/bit.24781
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protein a cycle number on the performance and lifetime of an anion exchange polishing step

Abstract: Most mAb platform purification processes consist of an affinity capture step followed by one or two polishing steps. An understanding of the performance linkages between the unit operations can lead to robust manufacturing processes. In this study, a weak-partitioning anion-exchange chromatography polishing step used in a mAb purification process was characterized through high-throughput screening (HTS) experiments, small-scale experiments including a cycling study performed on qualified scale-down models, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…For the 600 and 100 μL columns, turbidity breakthrough occurred at earlier stages of loading as cycle number increased. These results are consistent with previous work conducted with the control condition using a 2.9 mL lab scale column (Iskra et al, ) and indicate loss of impurity capacity due to resin fouling. Differences in bed height and experimental residence times between RoboColumn scales were observed to result in different degrees of fouling.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the 600 and 100 μL columns, turbidity breakthrough occurred at earlier stages of loading as cycle number increased. These results are consistent with previous work conducted with the control condition using a 2.9 mL lab scale column (Iskra et al, ) and indicate loss of impurity capacity due to resin fouling. Differences in bed height and experimental residence times between RoboColumn scales were observed to result in different degrees of fouling.…”
Section: Resultssupporting
confidence: 93%
“…The need for a depth filter revealed, however, that cleaning the resin with 2 M NaCl and 0.5 M NaOH was insufficient in removing all types of potentially fouling components. Resin that had been fouled over multiple processing cycles could not be retroactively restored with 1 M acetic acid, 6 M guanidine hydrochloride, 8 M urea, or 100% acetonitrile (Iskra et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reported progress in this area includes the use of an adsorptive hybrid filter and adsorptive depth filters for the removal of process‐related impurities such as HCPs, DNA, viruses, and soluble aggregates . The advantages of impurity clearance during secondary clarification may include improved product purity post‐Protein A capture, improved viral clearance performance, and reduced impurity challenges to the downstream polishing columns and filters . Depth filtration can remove precipitated impurities via physical sieving, but also soluble impurities through a combination of adsorptive mechanisms such as electrostatic and hydrophobic interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Foley et al [10] filtering yeast suspension of Saccharomyces cerevisiae (2 g L −1 ) on flat sheet membranes demonstrated that the deposition of particulate matter at the membrane surface could reduce access of fouling material inside the pores. The effect of interaction between yeasts or cell debris and molecular compounds such as proteins or lipids and their consequences on fouling have been pointed out in packed bed processes [4,11,12]. Bovine serum albumin (BSA) and yeast particles on the reversibility of cake formation during microfiltration were investigated [13,14]; these studies have suggested that protein fouling of the membrane and filtration resistance was reduced in the presence of cells.…”
Section: Introductionmentioning
confidence: 99%